Psychological Skills and their Relationship to the Performance Level of the Shooting Skill among Handball Juniors in Jordan - Sha’lan , Maen Ahmad Mahmoud (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to identify the psychological skills and their relationship to the level of performance related to shooting skills among junior handball players in Jordan. Methods: The descriptive approach was used, and the study population consisted of (237) handball players in Jordan (born in 2006/2007) who participated in the junior league for the season (2021/2022). The study sample consisted of (122) players who were chosen randomly. To determine the psychological skills, the scale designed by Bull et al. (1996) was used, consisting of (24) items, and the divided goal test was used to measure the accuracy of shooting. Results: The psychological skills of handball juniors in Jordan came in the following order: First, the skill of sports achievement motivation with a large degree, second, the self-confidence skill with a medium degree, third, the perception with a medium degree, fourth, the attention focus skill to a small degree, fifth, the skill of coping with anxiety to a very small degree, finally, the skill of relaxation which was nonexistent. The study recommended the existence of a positive correlation between all psychological skills (achievement motivation, self-confidence, perception, the focus of attention, coping with anxiety, and relaxation) and the level of shooting skill performance in handball. Conclusions: The study recommended developing the following psychological skills: attention focus, coping with anxiety, and relaxation for handball juniors.